PERHITUNGAN PDRB HIJAU SEKTOR KEHUTANAN DARI DEPRESIASI HUTAN DI KABUPATEN TANAH BUMBU - Mega Rumita; Muhammad Anshar Nur (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research was conducted to know : (1) to identify the value of depletion, degradation, and forest depreciation in Tanah Bumbu District. (2) can see the value of forestry sector Green GDRP in Tanah Bumbu District.This type of research according to explantive in the form of descriptive research, using survey methods, and type of data in the form of quantitative data which includes some calculations using the concept of Green GDRP. The data used is secondary data.The results showed that the value of the Green GDRP is smaller than Conventional GDRP. The results of the 2016 forestry sector Green GDRP calculation amounted to Rp. 99.327,82 Million, in 2017 amounting Rp. 93.046,67 Million, and in 2018 amounting Rp. 97.211,59 Million.Keywords : Forest. Forestry Sector Green GDRP. Tanah Bumbu Regency. Green GDRP Calculation Method